INTER-PARLIAMENTARY RELATIONS IN THE MODERN INTERNATIONAL POLITICAL PROCESS - Алишер Эшонкулов (Journal Park Publishing, 2023)
The article highlights the features of inter-parliamentary relations in modern world politics, examines theoretical approaches to the classification of existing inter-parliamentary institutions in the world, analyzes the practice of the Inter-Parliamentary Union and integration associations in the post-Soviet space, compares the involvement of the G20 countries in the activities of key IPIs.
Keywords: inter-parliamentary relations, inter-parliamentary institutions, IPI, Inter-Parliamentary Union, G20.